Implementasi Pelatihan Mandiri Platform Merdeka Mengajar dalam Meningkatkan Kompetensi Guru - Utomo, Utomo; Kusumawati, Dian (Dawuh Guru: Jurnal Pendidikan MI/SD, 2024)
This study aims to describe the implementation of teacher competency improvement through independent training using the Independent Teaching Platform (PMM) at Muhammadiyah Schools in Kendal Regency. Data collection using questionnaires and data analysis was carried out in a qualitative descriptive manner. The research found that all teachers in Kendal District Muhammadiyah School have been familiar with PMM since its initial launch. All teachers have used PMM for independent training. The number of teachers who completed one topic was 83% and 17% completed 3 topics. The topics of lesson planning, differentiated learning, assessment and projects to strengthen the profile of Pancasila students have not been resolved. The main obstacles to the implementation of self-training are lack of time, overcrowding of teaching duties and lack of support from school principals.